Pengaruh Pengetahuan, Kemudahan Penggunaan, dan Kemanfaatan Quick Response Code Indonesian Standart (QRIS) Terhadap Penggunaan E-Wallet : (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara) - Hasmidar Pohan; Mustafa Kamal Rokan; M. Ikhsan Harahap (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to determine whether knowledge, ease of use and usefulness of the Quick Response Code Indonesian Standard (Qris) have a significant effect on the use of E-wallet among FEBI UIN North Sumatra students. The population used in this research were all active students in 2020-2021, Faculty of Islamic Economics and Business, UIN North Sumatra, totaling 4,878 with a sample size of 100 respondents. The sampling technique in this research used Non Probability Sampling using Purposive Sampling. The research method used is a quantitative method with multiple regression analysis, and the data collection technique is carried out by distributing questionnaires. The results of this study show that knowledge has a significant effect on the use of e-wallets among Febi UIN North Sumatra students, ease of use has a significant effect on the use of e-wallets among Febi UIN North Sumatra students, and usefulness has a significant effect on the use of e-wallets among Febi UIN Sumatra students North. Knowledge, ease of use and usefulness have a significant influence on the use of e-wallets among Febi UIN North Sumatra students.